Gangguan Berbahasa pada Anak dan Implikasinya dalam Psikolinguistik: Penelitian - Alfina Damayanti; Tantri Widiyarti; Hayati Tu Zahro; Roudlotul Aulia; Hany Uswatun Nisa (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study analyzes the characteristics of language disorders in children and their psycholinguistic implications through a systematic literature review of articles from 2021–2025. It focuses on children aged 0–18 with language impairments, using data from international databases and thematic analysis. Findings reveal that language disorders are complex, involving phonological, semantic, grammatical, and pragmatic aspects with varying severity. For example, cleft lip and palate affect phonology but preserve semantics. Psycholinguistically, these disorders reflect the interplay of neurobiological, cognitive, and socio-emotional mechanisms. Affective factors also influence children's linguistic expression. Effective interventions include repetition- and articulation-based speech therapy and singing activities. Early intervention at ages 3–4 shows lasting benefits for phonological and morphosyntactic skills. The study recommends a multidisciplinary approach and longitudinal research to better understand language development in children.